(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article investigates the musnad as a distinct genre within the classical hadith sciences, tracing its lexical origins, its technical definitions as employed in the scholarly tradition, and the historical conditions that gave rise to its emergence as a systematic mode of hadith compilation. The study examines the methodological principles governing musnad works, the criteria by which they are classified into selected (muntaqa), critically annotated (muʿallal), and general (ʿamm) categories, and the various organizational schemes applied by their compilers. Attention is also given to the genre’s contribution to the preservation of transmission chains and its indispensable role in the disciplines of narrator criticism (jarh wa-taʿdil) and hadith authentication.